How we secured a COVID‐19 convalescent plasma procurement scheme in Japan. Issue 7 (12th June 2021) - Terada, Mari; Kutsuna, Satoshi; Togano, Tomiteru; Saito, Sho; Kinoshita, Noriko; Shimanishi, Yumiko; Suzuki, Tetsuya; Miyazato, Yusuke; Inada, Makoto; Nakamoto, Takahito; Nomoto, Hidetoshi; Ide, Satoshi; et al.
Abstract: Background: In order to tackle the COVID‐19 pandemic, a COVID‐19 convalescent plasma (CCP) procurement program was initiated in Japan in April 2020. The program was a collaboration between a government‐managed national hospital, an infectious disease research institute, and a blood banking organization. Each party assumed different responsibilities: recruitment, SARS‐CoV‐2 antibody profiling, and plasmapheresis; conduction of screening tests; and SARS‐CoV‐2 blood testing, respectively. Methods: We adopted a two‐point screening approach before the collected CCP was labeled as a CCP product for investigational use, for which we mainly tested anti‐SARS‐CoV‐2 antibody eligibility and blood product eligibility. Anti‐SARS‐CoV‐2 spike protein titer was measured using enzyme‐linked immunosorbent assay, and the IC50 value was denoted as the neutralizing activity. Blood donor eligibility was extended beyond the normal blood donation guidelines to include a broader range of participants. After both eligibility criteria were confirmed, participants were asked to revisit the hospital for blood donation, which is a unique aspect of the Japanese CCP program, as most donations are taking place in normal blood donation venues in other countries. Some donors were re‐scheduled for repeat plasma donations. As public interest in anti‐SARS‐CoV‐2 antibodies increased, test results were given to the participants. Results: As of September 17, 2020, our collection of CCP products was sufficient to treat more than 100 patients. As a result, projects for administration and distribution are also being conducted. Conclusions: We successfully implemented a CCP procurement scheme with the goal to expand to other parts of the country to improve treatment options for COVID‐19.